Differential diagnosis of liver disease in domestic dogs and cats - Локес, П. І.; Локес-Крупка, Т. П. (Scientific Progress & Innovations, 2014)
Found that liver disease is very common in pet dogs and cats. Shows the structure of the liver disease in animals of these species. Found that the differentiation of the most common diseases of the liver (hepatitis, cirrhosis and hepatodistrophia) in dogs and cats should be carried out by clinical signs, symptoms, results of ultrasound, as well as the results of laboratory analysis of blood. Describes the most typical symptoms of diseases and their characteristic ultrasonographic differences and blood biochemical parameters.